Uji Efektivitas Daya Hambat Ekstrak Etanol Daun Benalu Belimbing Macrosolen cochinchinensis (Lour) V.Tiegh Terhadap Bakteri Staphylacoccus aureus - Supartiningsih; Anna Maria Saragih Turnip (Universitas Sari Mutiara Indonesia, 2023)
Benalu Belimbing is traditionally used to treat cancer, stop bleeding in wounds and to treat wounds as well as anti-bacterial and skin diseases. Staphylococcus aureus bacteria are bacteria that are normal flora found on the skin, nose and respiratory tract, diseases that appear such as acne, boils, ulcers, wounds and pneumonia. This research was carried out with the aim of determining the antibacterial activity of ethanol extract of Benalu Belimbing leaves (Macrosolen cochinchinensis (Lour) V.Tiegh) with concentrations of 20%, 40%, 60% and 80% against the growth of Staphylococcus aureus bacteria. This research method uses an experimental method, namely to determine the antibacterial activity of ethanol extract of Benalu Belimbing leaves (Macrosolen cochinchinensis (Lour) V.Tiegh) on the growth of Staphylococcus aureus bacteria. This research used 96% ethanol solvent. Testing was carried out in several stages including collecting materials, preparing simplicia, making ethanol extract from mistletoe starfruit leaves by maceration and testing antibacterial activity against Staphylococcus aureus bacteria. Based on the results of phytochemical screening tests, the thick extract of mistletoe starfruit leaves contains flavonoid, saponin, steroid/triterpenoid and tannin compounds. The results of the anti-bacterial activity test of the thick extract of mistletoe star fruit leaves against Staphylococcus aureus bacteria had an average inhibitory activity at concentrations of 20% (7.36 mm), 40% (8.97 mm), 60% (10.48 mm), and 80% (11.81 mm). As a comparison, Cloramfenicol 30 μg was used to produce an inhibitory power of 21.94 mm and the best results obtained were at a concentration of 80% which had an inhibitory power of 11.81 mm.